Fabrication of copper ion-substituted hydroxyapatite/Silk fiber/Methylcellulose composite: mechanical, antimicrobial, hemocompatibility, bioactivity and cytocompatibility evaluation - N Valarmathi; Shanmugam Sumathi (Results in Chemistry)
Herein, we reported the preparation of copper substituted hydroxyapatite (Cu-HAP) and fabrication of electrospun composites using Cu-HAP, SF (Silk fiber) and MC (Methylcellulose) by E-Spin method. Characterization techniques such as XRD (phase formation), FTIR (chemical bonds), SEM and EDAX (surface morphology and elemental composition) were carried out. Porosity measurement, swelling and mechanical properties were carried out to investigate the physicochemical properties of the fabricated electrospun composites. The hemocompatibility analysis indicated a hemolysis ratio < 2 %, which confirms the blood compatibility nature of the composite. Antibacterial activity of Copper hydroxyapatite/silk fiber/ Methylcellulose electrospun composite showed estimable activity against E.coli (zone of inhibition: 46 ± 0.94 mm) compared with pure SF/MC electrospun composite (33 ± 1.21). Bioactivity study confirmed the development of bone-like apatite on the surfaces of optimized (SF/MC 30 wt% of Cu-HAP) electrospun composite. Furthermore, MG63 cells were utilised to study the biocompatibility of the enhanced electrospun composite and good cell viability (99.93 ± 0.12 % using 25 μg/mL) was observed from microscopic image and the results showed that 30 wt% of Cu-HAP added polymer composite has outstanding osteoinductivity, biocompatibility, and antibacterial results, making it a very valuable aspirant for use in bone tissue engineering (BTE) applications to repair bone defects.